2014
DOI: 10.1027/1015-5759/a000191
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Inflexibility in Pain Scale (PIPS)

Abstract: Psychological flexibility receives increasing attention as the overarching process in Acceptance and Commitment Therapy (ACT). This study investigates the psychometric properties of the Psychological Inflexibility in Pain Scale (PIPS), measuring “avoidance” and “cognitive fusion” with pain, in a heterogeneous clinical sample of 428 chronic pain patients from four rehabilitation centers. Furthermore, the relationship between the PIPS and mindfulness (Five Facet Mindfulness Questionnaire, FFMQ) as a theoreticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
5
28
0
Order By: Relevance
“…This version was related to anxiety (r = 0.54), pain catastrophizing (r = 0.62), and pain acceptance (r = -0.72). Also, another study showed the correlation between PIPS and mindfulness in patients with chronic pain (17). The confirmatory factor analysis (CFA) of German version of this scale in 182 patients with chronic back pain confirmed the main bifactor structure.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This version was related to anxiety (r = 0.54), pain catastrophizing (r = 0.62), and pain acceptance (r = -0.72). Also, another study showed the correlation between PIPS and mindfulness in patients with chronic pain (17). The confirmatory factor analysis (CFA) of German version of this scale in 182 patients with chronic back pain confirmed the main bifactor structure.…”
Section: Introductionmentioning
confidence: 76%
“…Based on these results, the avoidance subscale was introduced as the appropriate scale, but it was not the case with the cognitive fusion subscale (18). Also, in the study by Trompetter et al (17), showed the problems with the cognitive fusion subscale. However, despite the frequent use of this scale in other countries, no study examined the psychometric features of this scale in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The Psychological Inflexibility in Pain Scale (PIPS) assesses psychological inflexibility (Trompetter et al, 2014 ; Wicksell, Lekander, Sorjonen, & Olsson, 2010 ). Two items of the subscale experiential avoidance were used in this study, formulated as ‘Today I… (1) ..avoided doing things when there was a risk it would hurt or make things worse, (2) ..postponed things because of my pain complaints.’ Response alternatives ranged from (0) ‘not true’ to (10) ‘very much true’, with higher scores indicating more experiential avoidance.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, PIPS has been translated to Spanish, 15 Dutch, 16 German, 17 Iran, 18,19 Greek, 20 and Chinese 21 shown to have acceptable validity and reliability. However, there is yet no Japanese version of the PIPS.…”
Section: Introductionmentioning
confidence: 99%